Strategi Pengembangan Komunikasi Massa Dalam Mendukung Pembangunan Pertanian Dengan Pendekatan Jati Diri Bangsa Yang Berorientasi Pada Budaya - Cahyono Tri Wibowo; Sumardjo .; D. Hafidhuddin; S. S Agung (Institut Pertanian Bogor, 2011)
Abstract The results of analysis about the nation'smorality decline causes by lack of filteringtheinterferenational culture morality, the nation's culturaldamage, and lack of the educationalmode forthe communitycharacter. Condition ofthe nation's culturaldamage causes by the influences offoreignculture (Westernization), lack of educationand theunderstanding and practising of religion, and lack of preservation ofthe nation'snoblecultural values. The effects of that causes are the national identity decline and lack ofcommunity participationin supportingagricultural development, and the end is lessdevelopment ofmass communicationsin supportingagricultural developmentwiththe nation'sidentity approach based on the culture orientation.The improvement of Indonesia nation’s moralitycan be done by the establishment and enforcement of govermentpoliciesare neededin order tofilter thenation's culture, keepingthe noble values ​​ofnational culture, and increasing the charactereducation/nation’s character. Keepingthe noble values ​​ofnational culture can be done by promoting the valuable of nation's culturalvalues, practices thereligiousvalues​​into real action, and continuous the preservingnational culture and monitoring ofthatactivities. If the moralityof Indonesia nations is improved then communityparticipation increased and the national identity is more solid, the last societyhasan activeparticipationinthe development ofmasscommunicationwiththe nation'sidentity approach that oriented to theculture of Indonesia. Key words: fixed the Indonesia nation’s morality